The Impact of Tourism Service Quality in Improving Mental Imagery: A Study of Tourism Companies in Erbil, Kurdistan Region of Iraq (International Journal of Psychosocial Rehabilitation, 2020)
The ultimate goal of this research was to examine the impact of tourism service quality in improving the mental imagery from the managers' perspectives working for tourism companies in Erbil. Also, understand the concept of tourism service quality and its various dimensions. However, to collect empirical data, the researchers used a self-designed survey questionnaire. The survey sample comprises 136 managers, who were randomly selected from different tourism companies to reply to the survey questions. The empirical data were analyzed using a partial least squares structural equation modeling (PLS-SEM), which is a common analysis method for assessing models, in particular with latent variables and their correlations. The findings confirmed that tourism service quality impacted the mental imagery of tourists in destination facilities in Erbil, which contributes to tourist satisfaction and attracting tourists. The tourism service quality plays a vital role by increasing the level of tourist satisfaction through improving mental imagery. The results in this research supported the evidence that tourism service quality dimensions positively and significantly contribute to improving the mental imagery.